Digital Transformation Success Achieving Alignment and Delivering Results with the Process Inventory Framework - Schank, Michael (Berkeley, CA : Apress : Imprint: Apress, 2023)
Discover the key to digital transformation success in this comprehensive guide. In today's rapidly advancing technological landscape, companies are promised innovative business models, enhanced customer experiences, and productivity improvements through digital initiatives. However, it's disheartening that 70% of these endeavors fail to meet their goals, resulting in lost investments and frustrated stakeholders. The root cause of these failures often lies in the lack of alignment across organizations. Achieving alignment is crucial, encompassing both vertical alignment - which involves aligning goals from the CEO down to even low-level single contributors - and horizontal alignment - which enables seamless collaboration across functional areas. To address this challenge, Digital Transformation Success introduces Process Inventory, a powerful framework that not only establishes a common language but also aligns resources throughout the organization, driving a new level of operating efficiency and agility necessary to thrive in this digital era. This book delves beyond guiding principles, providing you with detailed methods, modeling techniques, operating models, and real-world case studies. By leveraging the Process Inventory framework, your organization can enhance existing disciplines like Change Management, Risk Management, and Operational Excellence, enabling effective digital technology design and propelling you into the forefront of the digital age.
Part I- Foundations for Success -- Chapter 1: The Key to Digital Transformation -- Chapter 2: Overview of the Process Inventory Framework -- Chapter 3: Defining the Digital Transformation Program.= Part II: Applying Process Inventory to Transform Ways of Working -- Chapter 4: Transform the Change Process -- Chapter 5: The Technology Path to Digitization -- Chapter 6: Drive Enterprise Efficiency -- Chapter 7: Fortify Risk Management -- Part III - Implementing the Process Inventory Framework -- Chapter 8: Operating Model and Accountability Framework -- Chapter 9: Creation Process and Modeling Rules -- Chapter 10: Tooling and Data Infrastructure. References.
Keywords: Technological innovations; Information technology -- Management; Artificial intelligence -- Data processing; Innovation and Technology Management; Business IT Infrastructure; Data Science